Building the Guatemalan Interagency Task Force Tecún Umán Lessons Identified - Oak, Gillian S. (RAND Corporation, 2015)
Guatemala receives counternarcotics aid from the United States. The president of Guatemala established the Interagency Task Force (IATF) Tecún Umán to develop domestic counternarcotics capability. USSOUTHCOM intends to use it as a model for developing new units in similar regions in the area. This report demonstrates how lessons learned inform future IATF development and provides recommendations for resolving remaining IATF challenges.